RESPONSE OF EELS (Monopterus sp) TO VARIOUS TYPE OF FEED - Abidin, Zaenal; Lumbessy, Salnida Yuniati; Lestari, Dewi Putri; Alim, Sahrul; Rahmadani, Thoy Batun Citra (Jurnal Perikanan Unram, 2025)
Eel seeds for aquaculture are primarily sourced from the wild. These seeds respond poorly to feed during the initial rearing phase. Therefore, this study aimed to provide feed that eels can consume in the early stages of culture. This study used an experimental method by testing the level of eel acceptance for natural feed, namely worms (Lumbricus sp.), golden snails (Pomacea sp.), chicken intestines, and maggots (black soldier flies), which will then be used as attractants mixed with pellet flour. Based on the order of feed selection and the time duration of eel response to the feed, eels preferred earthworms and snails as feed compared to maggots and chicken intestines. However, the four tested feed types can be consumed by eels. Mixing earthworms with pellet meal in the form of paste feed was responded well by eels. Eels consumed more (p <0.05) pellet meal mixed with earthworms than feed that did not have earthworms added to it. The incorporation of earthworms as an attractant in paste feed, as much as 50%, produced the same eel growth (P> 0.05) as eels given 100% worms. It indicated that a combination of artificial feed and earthworms could facilitate the consumption of artificial feed by eels in the initial phases of culture.